Genetics of monogenic obesity 1 - Hebebrand, Johannes; Hinney, Anke (Henry Stewart Talks, 2015)
Twin, family, and adoption studies, Central mechanisms involved in eating behavior, Genetic variation relevant for body weight regulation, Molecular synopsis – Parabiosis experiments, Cloning of the obese gene, Obesity syndromes, Monogenic forms of obesity – Leptin deficiency, Leptin signaling: adaptation to semi-starvation, Leptin and hypothalamic amenorrhea, Semi starvation induced hyperactivity „anorexia based hyperactivity“, POMC mutations in humans